Comparative Study of Montelukast with Dexamethasone for Possible Protection against Endotoxic Effect of Lipopolysaccharide in Male Mice - Alsaati, Rami Isam Kamal; Ahmed Hamed Jwaid (Iraqi Journal of Pharmaceutical Sciences, 2025)
Endotoxic septic shock (ESS) is a serious clinical syndrome caused by gram-negative bacterial infections. ESS refers to infected patients with high bloodstream endotoxin levels and activity and a high rate of cardiovascular, pulmonary, hepatic, and renal failure. The endotoxin in the bacterial cell wall can evoke neutrophil monocytes and secrete inflammatory mediators like cytokines, nitric oxide, histamine, and bradykinin, causing local and systemic inflammation, severe vasodilation, endothelial dysfunction, increased capillary permeability, vascular fluid extravasation, and disseminated intravascular coagulation. Mice were utilized as experimental animals for research by inducing endotoxemia or a septic-like condition that closely simulates septic shock in humans via administering lipopolysaccharide (LPS) isolated from a particular bacterial strain at an appropriate dose. This study examined whether montelukast and dexamethasone protect male mice from LPS-induced endotoxicity. Twenty-eight Albino mice were randomly assigned to four groups (seven per group): Group I (control) mice were given 0.25–0.5 ml of distilled water by oral gavage once daily for a week and euthanized on the 8th day. Group II mice received 10 mg/kg intraperitoneal LPS and were euthanized on the second day. Group III mice received oral gavage dexamethasone 2.5 mg/kg once daily for a week. Two hours following the final dosage, LPS was given and euthanized on the 8th day. Group IV mice received oral gavage montelukast (20 mg/kg) once daily for a week. Two hours after the last dose, LPS was given and euthanized on the 8th day. Results show that pretreatment with both drugs lowers serum TNF-α, IL-6, RANK, and OPG levels, as well as cathepsin-G and neutrophil elastase gene expression. In conclusion, montelukast may have a promising protective effect from LPS-induced endotoxicity and may be an option as a protective drug from inflammatory consequences in humans.